PENGARUH PENCAHAYAAN, POSISI KERJA DAN GENDER TERHADAP PRODUKTIVITAS VISUAL INSPECTION TASK - Pasmawati, Yanti; Kusmindari, Christofora Desi; Sukapto, Paulus; Octavia, Johanna Renny (Jurnal Rekayasa Sistem Industri, 2017)
Visual inspection task is the inspection activity of a product with the eye position centered over the moving conveyor, the faster the product is produced, the more critical the time of the inspection operator. The conditions in the long term will result in a decrease in productivity (Manuaba, 1992). The research objective to be achieved, among others: (1) Determining the optimal level of productivity based on the studies measure of performance checks on experimental design in every visual inspection task beverage packaging cup "Panther". (2) Determine the influence of lighting, working position and gender on the productivity of visual inspection task on beverage packaging. The object of research is part operator checks on beverage packaging cup "panther". Here are 10 people who have IQ scores of 90-120 aged 20-25 years. The research method was experimental method. The independent variables consist of lighting levels, working position, and gender. Variable manipulated into 12 groups experimental design. Data processing is done by checking the performance measurement approach. Analysis of experimental data using Analysis of Variance (ANOVA), and productivity. The study states that: (1) the highest labor productivity LkB200 experimental design (male, standing working position, the lighting level of 200 Lux) for 0.833. But the productivity of all design experiments have not reached optimal productivity, (2) Areas of different interactions in experimental design factor is the level of lighting in the working position. These factors affect the number of detected defects and work productivity.Keywords: Lighting, Measurement Time, Productivity, Performance Measures Inspection, Analysis of Variance (ANOVA)Â